The Mechanical Properties and Microstructure Analysis of Carbon Structural Steel After Quenching in Circulated Water Medium - Rosidah, Afira Ainur; Setyowati, Vuri Ayu; Suheni, Suheni; Febrianto, Muhamad (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
The use of carbon structural steel in construction is widely developed. It is important to do research continuously in order to get the optimum mechanical and physical properties of a material. Heat treatment which includes heating and quenching is a process that can be carried out to improve mechanical properties. A fast cooling rate is used to obtain higher strength and hardness. This research studied the effect of quenching using circulated water medium with water flow rate variations in structural steel Q235, Q255, and Q275 to their mechanical properties and microstructure. The heat treatment process was done with hardening at 1150oC, roll milling at austenitizing temperature, then quenching using circulated water medium with water flow rate of 225, 238, 247 m3/h. The tensile and hardness test results showed that water flow rate and carbon content in steel give an effect on strength and hardness. The highest tensile strength and hardness value were achieved by Q275 steel with a flow rate of 247 m3/h, which are 73,49 kgf/mm2 and 298 HVN, respectively. Meanwhile, the microstructures resulted in the presence of the mixture of martensite and pearlite, as well as ferrite in every sample with the increase in the composition of martensite and pearlite in Q275 steel with a flow rate of 247 m3/h.